ASPECTS CONCERNING FINANCIAL PROFITABLENESS ANALYSIS AND ITS PURPOSE IN SUBSTANTIATION OF FIRM’S STRATEGIC FINANCING DECISIONS - Solomon, Daniela; Dragomirescu, Simona (Studies and Scientific Researches. Economics Edition, 2008)
Financial profitableness, relevant indicator in enterprises performance appreciation and of its position on the market, depends on the commercial policy (commercial profitableness), on the engaged capital’s efficiency (economic profitableness), on the policy and financial structure of enterprise (debt degree) offering information both to investors and managers, orienting the enterprise in financing strategic decisions.